Carbon trading amidst global uncertainty: The role of policy and geopolitical uncertainty - Adediran, Idris A.; Swaray, Raymond (Economic Modelling, 2023)
Economic policy uncertainty (EPU) and geopolitical uncertainty (GPU) can fuel speculation, flood the carbon trading market with excess allowances, and undermine the scheme's efficacy in tackling climate change. While the existing literature documents the adverse effects of uncertainty on macroeconomic and financial variables, the impact on the carbon trading risk remains unclear. This paper analyses the effects of EPU and GPU on the volatility and other risk levels in the carbon market using daily European Union Emissions Trading Scheme data (February 2, 2009 to 8/31/2022) and monthly data on the uncertainty indicators (2009M2–2022M8). The findings reveal that unstable policies and geopolitical tensions heighten carbon market risk since global uncertainty increases information asymmetry and risk premium and causes a delay in investment decisions. Future deliberation among the Cooperation of Parties under the United Nations Framework Convention on Climate Change should incorporate measures to mitigate global uncertainty while pushing for decarbonization and transition to clean technology.
Keywords: Carbon trading; Policy uncertainty; Geopolitical uncertainty; Decarbonization; Clean technology